Pengaruh Tingkat Suku Bunga Kredit, Prosedur Kredit, Kualitas Pelayanan dan Literasi Keuangan Terhadap Keputusan Pengambilan Kredit Konsumtif di PT. Bank Pembangunan Daerah (BPD) Papua Cabang Waisai Kabupaten Raja Ampat - Clara Juvita Indri Marleyn; Erric Wijaya; Muchlis Muchlis; Enny Haryanti (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of credit interest rates, credit procedures, service quality, and financial literacy on consumer credit decisions at PT. Regional Development Bank Papua, Waisai Branch, Raja Ampat Regency. The study used a quantitative approach with a survey method of customers with Civil Servant and Government Employees with Work Agreements status in Waisai City. Data were collected through an online questionnaire using Google Forms and analyzed using Structural Equation Modeling (SEM) techniques. The results showed that interest rates, credit procedures, service quality, and financial literacy had a significant positive effect on consumer credit decisions. These findings emphasize the importance of setting competitive interest rates, simple credit procedures, quality service, and improving customer financial literacy to encourage credit decisions.